The 1,2-intercompartmental supraretinacular artery vascularized bone graft for scaphoid nonunion: management and clinical outcome - Hirche, Christoph; Heffinger, Christian; Xiong, Lingyun; Lehnhardt, Marcus; Kneser, Ulrich; Bickert, Berthold; Gazyakan, Emre (The journal of hand surgery. [American volume], 2014)
Purpose - To evaluate the clinical outcome of 1,2-intercompartmental supraretinacular artery pedicled vascularized bone graft for scaphoid nonunion (SN). - Methods - A retrospective study was performed to evaluate patients with SN and treated with 1,2-intercompartmental supraretinacular artery pedicled vascularized bone graft between 1997 and 2010. Functional measures, quality of life by Short Form SF-36 questionnaire, and analysis of risk factors were included. - Results - Out of 39 patients who were eligible for the study, 11 were lost to follow-up. Out of the remaining 28 patients, union was achieved in 21 (75%). The mean length of follow-up was 63 ± 45 months. In hands with scaphoid union, the grip strength and the radioulnar active range of motion were less than the contralateral side but greater compared with patients with nonunion. Active extension-flexion was less compared with the noninjured hand but similar to patients with nonunion. Disabilities of the Arm, Shoulder and Hand (DASH) score decreased from 58 to 23 in dominant hands and from 46 to 13 in nondominant hands. Smoking was found to be a risk factor for nonunion. Patients with scaphoid union tended to higher scores in 8 domains of SF-36-Item Health Survey quality of life without significant difference. - Conclusions - Surgical treatment of SN with 1,2-intercompartmental supraretinacular artery pedicled vascularized bone graft provided a union rate comparable with other vascularized bone graft techniques. Previous scaphoid reconstruction with standard iliac crest bone graft was not associated with higher risk for secondary nonunion. There was an upward tendency seen in DASH score and quality of life after scaphoid union. - Type of study/level of evidence - Therapeutic IV.
Gesehen am 16.09.2020